Empowering Kadilanggon Village-Owned Enterprises through Dissemination of Undegradable Nutrients (RUNs) Rumen Supplement Technology to Increase Livestock Productivity in Klaten Regency - Muhsin Al Anas; Chusnul Hanim; Taufan Alam; Asih Kurniawati; Muhlisin; Priyonggo Suseno (Pascasarjana Universitas Mataram, 2025)
Klaten Regency is a food production area designated by the Province of Central Java. Livestock farming has the potential to be developed to improve the community's economy. Inadequate feed nutrient requirements have an impact on low livestock productivity. Farmers will also incur additional costs for feed procurement, which increases production costs and tends to be detrimental to farmers. The empowerment program aims to disseminate concentrate feed technology with the addition of Rumen Undegradable Nutrients (RUNs) supplements to the Kadilanggon Village-Owned Enterprise (BUMDes) in Wedi District, Klaten Regency. Rumen Undegradable Nutrients is a feed supplement technology that contains fat protection and protected amino acids (lysine and methionine) to increase livestock productivity. The implementation process consisted of 1) socialization of the program implementation plan, 2) training in the production of RUNs supplements, 3) production of concentrate feed with the addition of RUNs supplements, 4) testing of concentrate feed on livestock, and 5) monitoring and evaluation of program implementation. The empowerment program has increased the knowledge and skills of livestock group members regarding feed and concentrate production methods using RUNs feed supplement technology. Additionally, the developed feed factory has generated economic value and provided employment opportunities.